Depressed demand and supply - Baptiste Massenot; Giang Nghiem (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
We investigate the implications of experienced-based learning on consumption-saving and labor supply, two fundamental decisions in business cycle models. Using the Dutch Household Survey, we find that individuals who have experienced higher national unemployment rates over their lifetime save more, borrow less, and work less, after controlling for aggregate shocks, income, wealth, and demographics. Possibly explaining these behavioral responses, these individuals find it more important to save for retirement and to cover unexpected expenses, are more worried about losing their job, and dislike their job more. These results have implications for business cycle models and stabilization policies.
urn:nbn:de:hebis:30:3-507274
Keywords: E7; 330